2023
DOI: 10.1021/acs.nanolett.3c00594
|View full text |Cite
|
Sign up to set email alerts
|

Nanoprocessing of Self-Suspended Monolayer Graphene and Defect Formation by Femtosecond-Laser Irradiation

Abstract: We demonstrate the femtosecond-laser processing of self-suspended monolayer graphene grown by chemical vapor deposition, resulting in multipoint drilling with holes having a diameter of <100 nm. Scanning transmission electron microscopy revealed the formation of many nanopores on the laser-irradiated graphene. Furthermore, atomic-level defects as well as nanopores were found in the graphene membrane by high-resolution transmission electron microscopy, while the overall crystal structure remained intact. Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Subsequently, this FeCo@Biomass precursor underwent rapid carbonization by laser scribing to generate FeCo@NGB. The laser’s photothermal effect causes rapid energy deposition, leading to the carbonization (Figure S1b), graphitization and exfoliation of the FeCo@NGB precursor, along with the generation of abundant C-defect sites. , The presence of abundant defect sites and N sites formed through self-doping can effectively hinder the aggregation of Fe and Co metals …”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, this FeCo@Biomass precursor underwent rapid carbonization by laser scribing to generate FeCo@NGB. The laser’s photothermal effect causes rapid energy deposition, leading to the carbonization (Figure S1b), graphitization and exfoliation of the FeCo@NGB precursor, along with the generation of abundant C-defect sites. , The presence of abundant defect sites and N sites formed through self-doping can effectively hinder the aggregation of Fe and Co metals …”
Section: Resultsmentioning
confidence: 99%
“…Pulsed laser ablation has been reported for the patterning of supported graphene, 39–41 and recently with suspended graphene. 25 Important is the ultra-fast laser ablation that refers to the phonon related characteristic time or heat transfer speed in materials. If lasers are nanoseconds (ns)-pulsed, then the delivered light can be converted to heat and spread to the neighboring regions, heating them up, melting, and ultimately resulting in undesired damage.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we established an optimized anthracene transfer method inspired by previous reports, 23,24 and developed fast-pulsed laser ablation to obtain microporous membranes. Even though fast-pulsed laser ablation has been recently investigated for the patterning of supported graphene, 25 its use on suspended graphene remains very limited/restricted due to its limited resolution. Here the large dimensions of the suspended graphene allowed us to study in detail the impact of the pulse intensity on the perforation size for 1, 2 and 4 layer graphene and to determine the ablation threshold.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy was used for the precise and rapid fabrication of mesoscale binary optical elements with microscale characteristics. Recently, Naohiro et al [48] demonstrated the treatment of self-suspended monolayer graphene with a spatial reshaping femtosecond laser using SLM, which enables multi-point drilling of holes with diameters smaller than 100 nm. The SLM is used as a four-fold symmetric 2D phase grating to realize multi-point processing with interference of multiple beams.…”
Section: Spatial-temporal Pulse Shaping Processingmentioning
confidence: 99%